The four-day win end your diet war and achieve thinner peace - Beck, Martha Nibley, 1962- (New York, NY : Simon & Schuster Audio, 2007)
Millions of people following typical weight-loss programs are actually programming themselves to get fatter. The Four-day win reveals how to change the way you eat four days at a time, by reversing the brain-body programming so you can create a leaner and healthier budy
Title from container
Keywords: Reducing diets; Reducing diets -- Psychological aspects; Happiness; Self-realization